Expression and Purification of Leu437Pro-Gly494Asp and Gly494Asp-Lys554Glu Recombinant Catalase-Peroxidase from Mycobacterium tuberculosis - Egrina Adiniko, Mercy
Tuberculosis (TB) is a contagious infectious disease in humans caused by Mycobacterium tuberculosis (M. tuberculosis). M. tuberculosis secretes enzymes named catalase-peroxidase (KatG) which could activate isoniazid (INH), a pro-drug for TB treatment. The presence of M. tuberculosis strains that are resistant to INH is caused by mutations in the katG gene encoding KatG. One strain of M. tuberculosis which is resistant to INH is a L10 clinical isolate containing katG with five mutated nucleotides. The relationship of a single mutation in each five-type mutations in KatG L10 with a reduced activities as a catalase, a peroxidase, and an INH-activator was already studied. However, similar studies involving double- mutation has not been done. This research aims to study the relationship between double- mutation in KatG Leu437Pro-Gly494Asp and Gly494Asp-Lys554Glu and the catalase activity of KatG. To achieve the target, katG without mutation and with double-mutation were expressed in Escherichia coli MC 1061, three recombinants KatG then were purified by the Ni-NTA affinity chromatography, and the catalase activity of all three types of KatG was determined by the H2O2 decomposition method, measured in 240 nm. KatG without and with two double-mutation were expressed in large amounts (overexpression) and dissolved in buffer. Purification results of the three-type KatG showed a protein band with ~80 kDa molecular weight in Sodium Dodecyl Sulphate-Polyacrylamide Gel Electrophoresis (SDS- PAGE) correlated with the KatG size. KatG Leu437Pro-Gly494Asp and Gly494Asp- Lys554Glu mutant had increased specific catalase activity, respectively 41.55 and 71.39% compared with that of KatG without mutation. The increase in catalase activity in both KatG mutants is not compatible with the previous result because five mutations in KatG eliminated 75–95% of catalase activity, peroxidase activity, and the KatG ability to activate INH. This result needs to be confirmed using the catalase activity assay with the same amount and quality of KatG.